Exploring Jordanian women's resistance strategies to domestic violence: A scoping review - Alsawalqa, Rula Odeh; Alrawashdeh, Maissa N.; Sa'deh, Yara Abdel Rahman; Abuanzeh, Amal (Frontiers in Sociology, 2022)
Despite there being an abundant gender and social science research on domestic violence (DV) in Jordan, particularly during the COVID-19 pandemic, there is limited understanding and knowledge of women's resistance strategies to DV. To fill this gap, this study conducted a scoping review to synthesize and analyze 11 articles published in English-language scholarly journals between 2001 and 2021 by following the PRISMA-ScR guidelines. The databases of the University of Jordan Library, Dar Almandumah, PsycINFO, PubMed, Google Scholar, and Scopus were searched in December 2021. Our review found no scientific articles that primarily discussed Jordanian women's resistance to DV and explicate it as a secondary aim within the context of screening for the causes, consequences, and prevalence of DV. Therefore, while a few articles implicitly conceptualized women's resistance in the context of the patriarchal structure—either as tactics of physical, social, economic survival, and to protect their family and honor, or as consequences of DV—no article provided an explicit definition of this concept. The articles also deliberated on 12 resistance strategies that women use to deal with DV; predominant among them are daily resistance, activities hidden for immediate and de facto gains (e.g., to avoid beatings, divorce and family disintegration, the decision to keep their children, and maintaining economic stability). The most common strategies are silence and not seeking help, reporting to family members or friends, seeking legal and social advice, and reporting to the police or healthcare provider.